PENEREPAN METODE “LEARNING FROM INCIDENTS” PADA SEBUAH TERMINAL PETI KEMAS - Rina Widya Astuti; Bina Kurniawan; Hanifa Maher Denny (Jurnal Kesehatan Masyarakat (Undip), 2018)
Learning from incidents is one of Occupational Safety and Health aspects which aimed to reduce accidents by learning from the previous incidents. One of industry type that requires the application of learning from incidents methods is container terminal. PT. X was a cargo handling company.It was recorded that 60 accidents occured on 2016 - 2017 and 5 of it caused fatality. The purpose of this research was to analyze the implementation of learning from incidents method in a Container Terminal. This research was a qualitative research. This research utilized purposive sampling technique. The investigator recruited three informants and nine triangulation informants. The instruments that used in this study were in-depth interview guides and document observation sheets. The results showed that PT. X has implemented the entire process of learning from incidents cycle. The company is in need to improve some aspects of applying the learning from incidents method from incident reporting, incident analysis, corrective action planning, implementation of corrective actions, follow-up corrective action and evaluation.